Schizophrenia: adherence to treatment and beliefs about the disorder and the drug treatment - Nicolino, Paula Silva; Vedana, Kelly Graziani Giacchero; Miasso, Adriana Inocenti; Cardoso, Lucilene; Galera, Sueli Aparecida Frari (Revista da Escola de Enfermagem da USP, 2011)
This study verified the adherence of people with schizophrenia to the medication, identified and compared their beliefs about the disorder and the drug among patients who adhered and those who did not. Participants were 14 patients of a psychiatric outpatient clinic. Semi-structured interviews and the Morisky-Green test were performed. The data was analyzed using a quali-quantitative approach. Results showed that 64.3% of patients do not adhere to treatment. Most participants considered the drug capable of reducing the seriousness and severity of the disorder. However, the drawbacks for patients that did not adhere to the treatment were more expressive. Side effects were the cause for interrupting the treatment for 80% of patients who intentionally did not adhere to treatment. It was observed there is insufficient knowledge about schizophrenia and the drug treatment. Patients referred to faith as a strategy to cope with the process they were experiencing. This study points at the need for strategies directed towards the promotion of drug treatment adherence among people with schizophrenia.